Bacteriological Profile and Antibiotic Susceptibility of Blood Culture Isolates in Intensive Care Units of a Tertiary Care Hospital: Pharmaceutical Science-Microbiology - Nishanthy, M; Saikumar, Chitralekha (International Journal of Life Science and Pharma Research, 2022)
Intensive Care Units infections have been found to be highest amidst the nosocomial infections. Sepsis results in increased morbidity and mortality rates. In order to decrease mortality and morbidity rates associated with sepsis, intensivists should have a keen knowledge of the existing bacteriological flora and their antibiotic susceptibility pattern. In this study, we aim to determine the prevalence of current bacteriological profiles in blood cultures, along with their antibiogram from Intensive Care Unit patients. This project was a retrospective cross-sectional study carried out for the duration of one year from December 2018 to 2019 in the Central lab, Microbiology department at tertiary care hospital, from patients suspicious of some blood stream infections like sepsis or other risk factors for it. From ICU, the number of blood samples received was 1440 in our Central Microbiology laboratory. All the samples received in the microbiology central lab were processed, and laboratory data, including bacteriological profile and antimicrobial susceptibilities were analysed. From ICU, the number of blood samples totally received were 1440 in our microbiology laboratory. Identification of isolates was done by colony morphology, Gram stain and standard biochemical reactions. Antibiotic susceptibility pattern was conferred by Clinical and Laboratory Standards Institute guidelines. Total number of positive cultures present in the study was 156(10.8%). Among these culture growth organisms, 82 were Gram positive (55.4%) isolates and 74 were Gram negative (50%). The most common isolate was Coagulase negative Staphylococcus trailed by Escherichia coli and Staphylococcus aureus, Acinetobacter species and Pseudomonas aeruguinosa, Klebsiella pneumoniae and Enterococcus species. Majority of the Gram positive isolates were susceptible to Linezolid, vancomycin and clindamycin. All the Gram negative isolates were susceptible to Carbapenems ,with susceptibility rate of 97% for E. coli, 93% for Acinetobacter, 93% for Pseudomonas aeruguinosa and almost all these isolates showed 100% susceptibility to Colistin and Polymyxin-B.